Effect of enamel matrix derivative protein on the healing of standardized epithelial wounds: a histomorphometric analysis in vivo - Al‐Hezaimi, Khalid (Int Wound J, 2011)
The enamel matrix derivative (EMD) is a preparation of the enamel matrix proteins secreted by the Hertwig's epithelial root sheath. It has been shown that EMD promotes periodontal wound healing; however, the significance of the protein in repairing skin wounds is insufficiently addressed. The aim of this in vivo histomorphometric investigation was to analyse the effect of EMD protein on the healing of standardised epithelial wounds. Dorsal skin of 22‐week‐old female guinea pigs (n = 33) was scarified and divided into test‐ (topical application of EMD) and control‐sites (sutured and allowed to heal). Animals were euthanised at specific time intervals and the specimens were then evaluated histomorphometrically. The mean widths of the external wound gaps (WGs) in the test‐ and control‐sites at the 5th, 20th and 35th day of healing were 5·89, 3·6 and 1·01 mm and 6·41, 5·02 and 3·43 mm, respectively. Histomorphometric analysis showed a statistically significant difference in the WGs between the test‐ and control‐sites. A significant increase in the formation of organised connective tissue matrix, collagen fibres and early muscle formation was observed in the test‐sites as compared with the control‐sites. Within the limits of this study, it is concluded that topical application of the EMD on standardised epithelial allows early wound closure and promotes healing as compared to when the defects are merely sutured.